MENGELOLA KAMPUNG DENGAN KEARIFAN LOKAL; Belajar dari Kampung Gampingan di Yogyakarta - Pramudito, Sidhi (Jurnal Arsitektur Komposisi, 2017)
Abstract: In recent years many new and modern buildings have emerged in Yogyakarta, on the other hand the existence of kampongs and the natural environment continues to decline, including local wisdom in managing the environment is increasingly abandoned. Kampung Gampingan as a "kampung kota" in the city of Yogyakarta, located on the riverside of the Winongo River. Kampong administrators and itâ€™s citizen Gampingan cooperate to manage and maintain the quality of the kampong environment. For them, the aspect of environmental conservation is very important and considered because it aims to maintain harmonious relationships between humans and the natural environment. The purpose of this paper is to explore information about environmental management in kampong Gampingan, which involves citizens and consider the impact on the natural environment. The results show that community participation, partnerships with various parties (other communities, universities, government and private), and the role of facilitators are very important in the management of kampong based on local wisdom. Community participation is the key to the success or failure of kampong management based on local wisdom.Keywords: kampong management, community participation, local wisdomAbstrak: Dalam beberapa tahun akhir-akhir ini banyak bangunan baru dan modern muncul di Yogyakarta, pada sisi lain keberadaan kampung dan lingkungan alamiah terus berkurang, termasuk kearifan lokal dalam mengelola lingkungan semakin ditinggalkan. Kampung Gampingan termasuk â€œkampung kotaâ€ di kota Yogyakarta, terletak di tepi Sungai Winongo. Pengurus kampung dan warga kampung Gampingan bergotong-royong mengelola dan menjaga kualitas lingkungan kampung. Bagi mereka, aspek pelestarian lingkungan sangat penting dan diperhatikan sebab bertujuan menjaga hubungan harmonis manusia dan lingkungan alam. Tujuan tulisan ini adalah menggali informasi tentang pengelolaan lingkungan di kampung Gampingan, yang melibatkan warga dan mempertimbangkan dampak terhadap lingkungan alam. Hasil penelitian menunjukkan bahwa partisipasi masyarakat, kemitraan dengan berbagai pihak (komunitas lain, perguruan tinggi, pemerintah dan swasta), dan peran fasilitator sangat penting dalam pengelolaan kampung yang berbasis kearifan lokal. Peranserta masyarakat menjadi kunci keberhasilan atau kegagalan pengelolaan kampung berbasis kearifan lokal.Kata kunci: mengelola kampung, partisipasi warga, kearifan lokal